2012
DOI: 10.4196/kjpp.2012.16.1.17
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Supramammillary Cells Projecting to the Hippocampus in Stress Response in the Rat

Abstract: The hypothalamus-pituitary-adrenocortex (HPA) axis is the central mediator of the stress response. The supramammillary (SuM) region is relatively unique among the hypothalamic structures in that it sends a large, direct projection to the hippocampal formation. It has been shown that mild stress could activate the SuM cells that project to the hippocampus. However, the role of these cell populations in modulating the stress response is not known. The present study examined the effect of stress on different popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…It was further reported (Aranda et al, 2006) that SUM lesions produced anxiolytic effects on an elevated T-maze. The latter finding is consistent with the demonstration of elevated levels of c-fos expression in SUM to novel environments (Ito et al, 2009; Wirtshafter et al, 1998), and results showing that select populations of SUM cells projecting to HF are affected by immobilization stress (Choi et al, 2012). …”
Section: Sum: Role In Learning and Memorysupporting
confidence: 88%
See 1 more Smart Citation
“…It was further reported (Aranda et al, 2006) that SUM lesions produced anxiolytic effects on an elevated T-maze. The latter finding is consistent with the demonstration of elevated levels of c-fos expression in SUM to novel environments (Ito et al, 2009; Wirtshafter et al, 1998), and results showing that select populations of SUM cells projecting to HF are affected by immobilization stress (Choi et al, 2012). …”
Section: Sum: Role In Learning and Memorysupporting
confidence: 88%
“…As might be expected by relatively widespread SUM projections to the limbic forebrain, the SUM has been associated with various functions including stress, anxiety, response to novelty, reward processes, and learning/memory (Aranda et al, 2006, 2008; Choi et al, 2012; Ikemoto, 2005; Ikemoto and Bonci, 2014; Ito et al, 2009; Shahidi et al, 2004a,b). Perhaps owing to the strong SUM projections to the septum and the hippocampus, disruptions of SUM have been shown to severely impair learning/memory over a range of tasks.…”
Section: Sum: Role In Learning and Memorymentioning
confidence: 87%
“…b). CA2 has connections to the paraventricular nucleus (PVN) and hypothalamic supramammilary nucleus, areas activated in response to threatening stimuli and important in modulating stress‐related alterations in learning and memory (Choi et al ; Cui et al ). We further detected ASIC1 and ASIC2 in all regions of the periaqueductal gray (PAG) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, substance P increases GABA release by acting on neurokinin-1 receptors, thereby enhancing local inhibitory responses in the hippocampus (Ogier and Raggenbass 2003) and entorhinal cortex (Stacey et al 2002). Interestingly, methods of inducing mild stress, such as exposure to an elevated plus maze (Silveira et al 1993) or immobilization (Choi et al 2012), have been shown to activate neurons in the SuM, presumably resulting in the release of substance P from SuM terminals in CA2. The effects of substance P on the physiology of CA2 pyramidal neurons are currently unknown.…”
Section: Org) (D)mentioning
confidence: 99%